Kontribusi Sistem Tanggung Renteng Dalam Membentuk Perilaku Anggota Dan Mewujudkan Zero Bad Debt - Dua Kleruk, Maria Yuniwati; Mitan, Wilhelmina; Maria Dilliana, Siktania (Jurnal Projemen UNIPA, 2026)
Savings and loan cooperatives play an important role in improving the economic welfare of their members. However, they frequently encounter the problem of non-performing loans (bad debt), which may threaten the institution’s financial stability. This study aims to examine the implementation of the joint liability system and and its contribution to shaping member’s behavior and achieving zero bad debt in the sudang sogor solot group at KSP Kopdit Sube Huter. A descriptive qualitative approach was employed using observation, interviews, and documentation collected during the internship period. The findings reveal that the joint liability system fosters discipline, responsibility, and solidarity among members through mutual supervision and shared accountability in loans and supports the achievement of zero bad debt. Therefore, the joint liability system serves not only as a financial risk management strategy but also as a social mechanism that strengthens member behavior and ensures the sustainability of the cooperative.